THE CONCEPT OF ’INTEGRATED DEVELOPMENT’: APPROACHES TO ITS IMPLEMENTATION IN THE SYSTEM OF PLANNING AND MANAGEMENT OF DE-OCCUPIED TERRITORIES RESTORATION - ZAPOTOTSKYI, Sergii; ZAIKIN, Sergii (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
The article examines the specifics of applying the concept of ’integrated development’ to form a system of governance and management decision[1]making in the interests of restoring the de-occupied territories. The scientific discourse on integrated development is examined through the prism of defining the essence of integrated development, its components, implementation in the system of territory development planning, introduction of new planning tools and changes in approaches to the use of the relevant traditional tools, and the experience of practical application of the concept in the interests of local and regional development. The concept, which significantly modernises the traditional system of territorial development planning in Ukraine, has been in practical use since 2010. The Concept of Integrated Development of a City or Territorial Community became the key document for implementing the approach. There are examples of this document being developed for individual territorial Hromadas, including rural ones. Our research shows a significant prospect of implementing the integrated planning approach for the de-occupied territories. The article analyses scientific approaches to understanding and applying the concept of ’integrated development’ to the study of local development and spatial planning. The key requests of the de-occupied Hromadas of the Kharkiv region regarding the destruction, vision of directions and the most urgent problems of restoring the de-occupied territories are identified. The long-lasting large-scale war has led to significant destruction, prolonged occupation of certain territories, and destroyed the logic and logistics of economic development of individual territorial Hromadas and regions. The article highlights the main features and characteristics of the de-occupied territories of Ukraine, as well as the main tools for planning and managing recovery. The restoration of the de-occupied territories and rethinking the development of territorial Hromadas requires the use of modern approaches and tools.